The Analysis of Life Strategies of Populations of Entomopathogenic Fungi in Gardens of Exclusion Zone of the Chernobyl Nuclear Power Plant - Drozda, Valentin (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The aim of researches was study the species composition, life strategies, spreading, ecology and biology of entomopathogenic fungi in gardens of exclusion zone of the Chernobyl nuclear power plant in context of the Chernobyl disaster, associated with the biodiversity of not only plants, animals, but also microorganisms. The analysis of some aspects of relationship between entomopathogenic fungi and various stages of development of the codling moth (Laspeyresia pomonella L.) was carried out, also investigated their saprophyte strategy. A row of key provisions that has relevant to theoretical and applied issues, including the specific factor of long-acting effect of ionizing radiations was allocated. The entomopathogenic fungi, as typical r-strategists, are characterized by signs of K-selection, develop in mature, climax microbial system on the biomass of caterpillars and pupae of the codling moth were shown. In addition, these entomopathogens can to develop in saprophytic conditions. The problems, associated with the implementation of tactics of reproduction, survival and trophic connections by fungi were discussed. The life strategy of the fungus – Paecilomyces farinosus A.H.S.Br. & G.Sm. was described in detail. The attention was focused on his dominance among other fungi with pronounced trophic expansion. The ecological adaptation and plasticity of Paecilomyces farinosus in saprophytic conditions are manifested clearly in spreading of pathogen in ecosystems of exclusion zone of the Chernobyl nuclear power plant. It is emphasized that one of the vectors of spreading of fungus is insects. The status of entomopathogenic fungi in ecosystems of exclusion zone of the Chernobyl nuclear power plant is determined by the balance of biomass and trophic resources, also the information role in this specific biocenotic structure.